Of Style and Stylistics: An Exploration of Linguistic and Literary Interplay in Anita Desai’s Cry, The Peacock and Voices In The City (International Journal of Food and Nutritional Sciences, 2022)
The study of style and stylistics has evolved significantly, transitioning from a focus on individual writer characteristics to a linguistic and structural approach. Traditionally, style was linked to metaphors, imagery, and symbols, but modern stylistics incorporates all linguistic elements, such as syntax, semantics, and narrative voice. Instead, style shapes meaning and defines an author's individuality. Stylistics bridges linguistics, pragmatics, and aesthetics, exploring how language forms a literary work's expressive essence. Modern approaches analyse language use across phonemes, sentences, and entire texts, focusing on elements like repetition, tone, and point of view. However, challenges persist, including subjectivity and the difficulty of correlating statistical norms with literary significance. Anita Desai exemplifies the psychological depth stylistics can uncover. Her novels, such as Cry, the Peacock and Voices in the City, eschew traditional linear progression, instead employing surrealistic imagery and fragmented narrative structures to convey the protagonist’s psyche. While embracing modern techniques, Desai retains traditional stylistic elements like metaphors and symbols, blending them seamlessly with innovative approaches. Ultimately, stylistics reveals the intricate interplay between language and literature, offering insights into a writer’s intent and the thematic resonance of their works.